Relationship Between Symptoms Duration and Acute Otitis Media Stage Patients at ENT Clinic of General Hospital University Muhammadiyah Malang - Setiawan, Indra; Miftha Churochman; Syahlum Marsha Irba; Andi Abdillah (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Otitis media ranked fifth in the global burden of disease and became the second leading cause of hearing impairment. Medical records data from the Ear Nose Throat (ENT) clinic of Muhammadiyah Malang University General Hospital (MMUGH) indicated that unspecified Acute Otitis Media (AOM) was the sixth most common disease in 2023. The duration of symptoms could indicate the stage of AOM, allowing for its elimination with prompt treatment. The objective of this research was to determine the relationship between symptom duration and the stage of AOM in patients at the ENT Clinic of MMUGH. The data used were primary data collected through interviews using a questionnaire. The analysis technique employed the Spearman correlation test and the sampling technique used purposive sampling. Statistically, there was no significant relationship between the symptoms duration and the stage of AOM.